ChemInform Abstract: Synthesis and Biological Evaluation of 3‐(4‐Chloro‐phenyl)‐4‐substituted Pyrazole Derivatives. Issue 46 (24th October 2013) - Horrocks, P.; Pickard, M. R.; Parekh, H. H.; Patel, S. P.; Pathak, Ravindra B.
Abstract Some of the newly synthesized compounds show potential biological activity.